PENGARUH GAJI DAN INSENTIF TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA UD. DNL KECAMATAN BANYUPUTIH KABUPATEN SITUBONDO - Arief, Mohammad Yahya; Soeliha, Siti; Kafi, Ahmad Atha'il (Fakultas Ekonomi dan Bisnis, 2023)
Human resources are a strategic factor in all organizational activities because human resources are the primary support for implementing organizational goals. This study aimed to determine the effect of salary and incentives on performance with job satisfaction as an intervening variable at UD. DNL Banyuputih District, Situbondo Regency. The population in this study were all employees of UD. DNL Banyuputih District, Situbondo Regency, totaling 40 people. The sampling technique used in this study was a saturated sample. This study's data analysis and hypothesis testing used Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that salary has an insignificant effect and impacts job satisfaction. Incentives have a significant effect and have an impact on Job Satisfaction. Salary has an insignificant effect and has an impact on performance. Incentives have an insignificant effect and have an impact on performance. Job satisfaction has a significant effect and has an impact on performance. Salary has a positive but insignificant effect on Employee Performance through Job Satisfaction. Incentives have a positive and significant effect on Employee Performance through Job Satisfaction.